IDENTITY CRISIS: PROBLEMS OF TEACHER FORMATION - Bugachuk, Tatyana; Khodyrev, Alexander; Когiakovtseva Olga; Zhedunova, Ludmila (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article is devoted to the problem of the crisis of personal and social identities as significant components of the “existential crisis” in the context of social transformation. Based on the ideas of existential phenomenology, the authors reveal the changing nature of the teacher identification system, suggest highlighting the notion of the “teacher identity” and consider the crisis nature of its formation. The authors revealed that the process of identifying future teachers is carried out in stages through the subsequent change of academic, educational, professional and professional identity. The transition from one type of identity to another occurs on the basis of identity crises.